Resource implications and health benefits of primary prevention strategies for cardiovascular disease in people aged 30 to 74: mathematical modelling study - Marshall, Tom (BMJ, 2002)
OBJECTIVE: To develop a model to determine resource costs and health benefits of implementing guidelines for the prevention of cardiovascular disease in primary care. DESIGN: Modelling of data from six strategies for prevention of cardiovascular disease. Strategies incorporated two ways of identifying patients for assessment: traditional (assessment of all adults) and novel (preselection of patients for assessment using a prior estimate of their risk of cardiovascular disease). Three treatment strategies were modelled in conjunction with each identification strategy. SETTING: England. SUBJECTS: Patients aged 30 to 74 eligible for primary prevention strategies for cardiovascular disease who were selected from a hypothetical population of 2000. MAIN OUTCOME MEASURES: Resource costs of assessing eligible adults, providing treatment and follow up to those eligible, and number of cardiovascular events this should prevent. RESULTS: Novel strategies prevented more cardiovascular disease, at lower cost, than traditional strategies. Some treatment strategies prevent more cardiovascular disease with fewer resources than others. The findings were robust across a range of different assumptions about workload. CONCLUSION: Preselecting patients for assessment makes better use of staff time than assessing all adults. Treating many patients with low cost drugs is more efficient than prescribing a few patients intensive antihypertensives and statins. Authors of guidelines should model workload implications and health benefits of following their recommendations.